Digit ratio (2D:4D) and amniotic testosterone and estradiol: an attempted replication of Lutchmaya et al. (2004). (21st December 2021) - Richards, Gareth; Browne, Wendy V.; Constantinescu, Mihaela
Abstract: The ratio of length between the second (index) and fourth (ring) fingers (digit ratio or 2D:4D) is frequently employed as a retrospective marker of prenatal sex hormone exposure. Lutchmaya et al. (2004) reported that the ratio of testosterone (T) to estradiol (E) present in second-trimester amniotic fluid was negatively correlated with digit ratios for the right hand (but not the left hand) in a sample of 29 children at 2-year follow-up. This observation is frequently cited as evidence for the measure's validity but has not been replicated. We therefore present the findings of another study of amniotic T and E that did not find evidence for these effects at 4½-year follow-up. The confidence intervals were large, the direction of correlations observed was generally erratic, and the overall findings question the premise that second-trimester sex hormones affect the development of digit length ratios in humans.